Small molecule–constrained paratope mimetic bicyclic peptides as potent inhibitors of group 1 and 2 influenza A virus hemagglutinins - Rameshwar U. Kadam; Jarek Juraszek; Boerries Brandenburg; Divita Garg; Xueyong Zhu; Mandy Jongeneelen; Chan Tang; Wim B. G. Schepens; Christophe Buyck; Bart Stoops; Jan Vermond; Ronald Vogels; et al. (Proceedings of the National Academy of Sciences, 2026)
Influenza continues to be a major threat to global health and a substantial economic burden. Innovative strategies are needed to tackle the growing resistance to established influenza therapeutics and to develop new therapeutics with novel mechanisms of action. Previous peptide and small molecule designs have been successful only against influenza group 1 hemagglutinin (HA). Here, we report on a CLIPS (Chemical Linkage of Peptides onto Scaffolds)-based approach to design potent peptidic inhibitors of influenza A viruses that now extend to both group 1 and group 2 HAs. This approach merges features of antibodies and small molecules to design constrained bicyclic peptides that engage the highly conserved HA stem. The heavy-chain complementarity-determining region 3 (HCDR3) of human broadly neutralizing antibody FI6v3 was grafted onto functionalized small molecule scaffolds. The designed peptides exhibited in vitro heterosubtypic cross-reactivity in binding to group 1 (H1 and H5) and group 2 (H3 and H7) HAs and in neutralization of H1N1, H5N1, and H7N3 viruses. A crystal structure of the bicyclic peptide with HA from H1N1 A/Puerto Rico/8/1934 (H1/PR8) at 2.35 Å resolution revealed that the designed peptide faithfully mimics the binding mode and functionality of the parent antibody FI6v3 to the highly conserved stem epitope. These structural and functional data illustrate how both group 1 and group 2 influenza A viruses can now be targeted by constrained peptidic ligands that should aid in development of pan-influenza therapeutics.